Weight control practices of Division I National Collegiate Athletic Association athletes. Issue 2 (2nd April 2016) - Wilson, Patrick B.; Madrigal, Leilani A.; Burnfield, Judith M.
ABSTRACT: Objectives : Altering body weight can have substantial effects on an athlete's performance and well-being. Limited information is available describing the weight control practices of Division I National Collegiate Athletic Association (NCAA) athletes. Methods : Weight control practices data from 188 (138 male and 50 female; 18-23 y) Division I NCAA athletes were analyzed as a part of this cross-sectional, retrospective study. Participants completed questionnaires on weight control practices and weight control nutrition knowledge at the end of their season and were classified into weight-sensitive and less weight-sensitive sports. Results : A higher proportion of females attempted to lose weight than males among less weight-sensitive sports (61% vs. 22%, chi-square = 15.8, p < 0.001). However, the prevalence of weight loss attempts was not different between females and males among weight-sensitive sports (50% vs. 60%, chi-square = 0.5, p = 0.479). The prevalence of weight gain attempts differed by gender for less weight-sensitive sports (65% vs. 4% for males and females, chi-square = 33.5, p < 0.001) but not weight-sensitive sports (24% vs. 9% for males and females, chi-square = 2.1, p = 0.146). Weight control knowledge did not differ between participants attempting versus not attempting to lose weight (Mann-Whitney U = 3340, z = -1.37, p = 0.17). Common maladaptive behaviors used to lose weight included skipping meals and exercising more than usual. Conclusion : Weight loss attempts are common among Division I NCAA athletes, and the differences between males and females may be more pronounced among less weight-sensitive sports. Weight gain attempts are more common in select male sports.